An investigation of metal oxides which are photoluminiscent at room temperature - Leite, E. R.; Pontes, F. M.; Lee, EJH; Aguiar, R.; Longo, Elson [UNESP]; Pontes, DSL; Nunes, MSJ; Pizani, P. S.; Lanciotti, F.; Boschi, T. M.; Varela, José Arana [UNESP]; Paskocimas, C. A.; et al. (Elsevier B.V., 2004)
Amorphous thin films, based on different network formers, were processed by a soft chemical process called the polymeric precursor method. The resultant amorphous metal oxides, displayed intense photoluminescence (PL) at room temperature. Heat treatment increases the PL intensity of these materials. Theoretical ab initio calculations are correlated with the observed experimental trends. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: thin films; room temperature; amorphous